Efficient Synthesis of Novel Plasticizers by Direct Palladium‐Catalyzed Di‐ or Multi‐carbonylations. (28th December 2022) - Hu, Yuya; Sang, Rui; Vroemans, Robby; Mollaert, Guillaume; Razzaq, Rauf; Neumann, Helfried; Junge, Henrik; Franke, Robert; Jackstell, Ralf; Maes, Bert U. W.; Beller, Matthias
Abstract: Diesters are of fundamental importance in the chemical industry and are used for many applications, e.g. as plasticizers, surfactants, emulsifiers, and lubricants. Herein, we present a straightforward and efficient method for the selective synthesis of diesters via palladium‐catalyzed direct carbonylation of di‐ or polyols with readily available alkenes. Key‐to‐success is the use of a specific palladium catalyst with the "built‐in‐base" ligand L16 providing esterification of all alcohols and a high n / iso ratio. The synthesized diesters were evaluated as potential plasticizers in PVC films by measuring the glass transition temperature ( T g ) via differential scanning calorimetry (DSC). Abstract : The first di‐ and multi‐carbonylations of olefins with di‐ or polyols provide a general and straightforward access to a variety of di‐ or multiesters with high efficiency and selectivity. Representative diesters show potential performance ( T g ) as novel plasticizers.